Relewancja a interpretacja tekstów literackich - Wilson, Deirdre (Wydawnictwo Naukowe UAM w Poznaniu, 2012)
There has been some discussion about how far relevance theory can help in analysing the interpretation of literary works. Starting from the assumption that literary works are not entirely sui generis but exploit at least some of the abilities used in other varieties of verbal communication, I show how the same theoretical machinery used in analysing the interpretation of ordinary utterances can shed light on the interpretation of literary texts, and touch briefly on two more general issues: how can fictional works be relevant, and how can illocutionary and perlocutionary effects be disentangled in the case of literary works? [translated by Deirdre Wilson].
Relevance and the interpretation of literary works